Customary Land Law in the Mamberamo Community - Pieth Rumaikewi, Yan; Sari, Liani; Burhan, Wahyudi (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study is entitled Law on Customary Land in the Mamberamo Community, Especially the Warembori Village Community in Tanah Tabi, Papua Province. The main focus of this study is to examine the agrarian conflict between the Warembori Village and Yoke Village communities in Mamberamo Hilir District, as well as to analyze the mechanism of recognition and protection of customary rights of customary law communities in the area. This study uses a qualitative descriptive method with a case study approach. Data were obtained through interviews with traditional figures, community leaders, and parties involved in land disputes. In addition, secondary data was collected from legal documents such as Law Number 5 of 1960 and Papua Provincial Regulation Number 5 of 2022 The results of the study indicate that this agrarian conflict was caused by overlapping claims to customary land. In addition, there are still obstacles in the implementation of legal protection for indigenous peoples, especially in the administrative aspect of land registration. This study provides recommendations to improve the recognition and legal protection of customary land through clearer and more inclusive regulations.